Relationship Between CPAP Termination and All-Cause Mortality: A French Nationwide Database Analysis - Pépin, Jean-Louis; Bailly, Sébastien; Rinder, Pierre; Adler, Dan; Benjafield, Adam V; Lavergne, Florent; Josseran, Anne; Sinel-Boucher, Paul; Tamisier, Renaud; Cistulli, Peter A; Malhotra, Atul; Hornus, Pierre (Chest, 2022)
Randomized controlled trials have failed to demonstrate an effect of CPAP therapy on mortality. However, these studies have a number of important limitations, including low CPAP adherence, patient selection, and a small number of mortality events. What are the effects of CPAP therapy termination in the first year on all-cause mortality in patients with OSA from the Nationwide Claims Data Lake for Sleep Apnea study? Data from the Système National des Données de Santé (SNDS) database, the French national health insurance reimbursement system, for all new CPAP users ≥ 18 years of age were analyzed. The SNDS contains comprehensive, individualized, and anonymized data on health spending reimbursements for > 99% of all individuals living in France. OSA diagnosis was based on specific disease codes, whereas CPAP prescription was identified using specific treatment method codes. CPAP therapy termination was defined as the cessation of CPAP reimbursements triggered by the respiratory physician or sleep specialist in charge of follow-up. Patients who terminated therapy in the first year were propensity score matched with those who continued to use CPAP. The primary outcome was all-cause mortality. Three-year survival was visualized using Kaplan-Meier curves. Contributors to mortality also were determined. Data from two matched groups each including 88,007 patients were included (mean age, 60 years; 64% men). Continuation of CPAP therapy was associated with a significantly lower risk of all-cause death compared with CPAP therapy termination (hazard ratio [HR], 0.61; 95% CI, 0.57-0.65; P < .01, log-rank test). Incident heart failure also was less common in patients who continued vs terminated CPAP therapy (HR, 0.77; 95% CI, 0.71-0.82; P < .01). These real-world data from a comprehensive, unbiased database highlight the potential for ongoing use of CPAP treatment to reduce all-cause mortality in patients with OSA.